Mapping Self-Care Interventions for Improving Quality of Life Among Patients with Hypertension: A Scoping Review - Pujikurniawati, Citra Reza; Ibrahim, Kusman; Purba, Chandra Isabella Hostanida; Fauzan, Naufal Hafizh (Chakra Brahmanda Lentera Institute, 2026)
Background: Hypertension is a leading cause of cardiovascular disease and premature death worldwide. Despite the growing use of multidisciplinary self-care interventions to support patient-centred hypertension management, evidence on their effectiveness in improving quality of life remains fragmented. This scoping review aims to map and synthesise the available evidence on the effectiveness of self-care–based interventions in improving the quality of life of patients with hypertension. Methods: This scoping review followed PRISMA-ScR guidelines, the PCC framework, and the JBI-refined Arksey & O’Malley methodology. Literature searches were conducted in PubMed, ScienceDirect, Scopus, and EBSCOhost (2021–2026). Eligible studies included experimental studies and systematic reviews involving treated hypertensive patients. After independent PRISMA-based screening by four reviewers, 13 articles were included. Data were appraised using JBI tools and synthesised through thematic analysis to classify intervention models by lead professionals, delivery modes, and key self-care components. Results: From 1,328 identified records, the literature spans a broad international scope; however, it remains dominated by studies originating in High-Income Countries (HICs) or those using advanced digital health infrastructures. In contrast, evidence on the specific impact of these interventions on quality of life in Low- and Middle-Income Countries (LMICs), including Indonesia, remains relatively limited. The synthesis results identified three main categories of self-care-based intervention models: (1) professional-led models (facilitated by nurses, pharmacists, physicians, or community health workers and multidisciplinary collaborative care models), (2) digital health delivery modes (including mHealth, tele-nursing, and hybrid models), and (3) structured self-care components (focusing on self-monitoring, medication management, lifestyle modification, and psychosocial support). Although these models have proven effective in significantly lowering systolic and diastolic blood pressure while enhancing patient self-efficacy and quality of life, a research gap remains regarding the lack of direct comparative analysis between models in resource-limited settings and the systematic evaluation of long-term psychosocial outcomes. Conclusion: Nurse-led, multidisciplinary, and technology-supported interventions can improve blood pressure control and quality of life in hypertension. Future research should evaluate their effectiveness and efficiency across different settings, particularly in Indonesia.